Method of completing missing data of soil temperature - POKLADNÍKOVÁ, Hana; ROŽNOVSKÝ, Jaroslav (Contributions to Geophysics and Geodesy, 2021)
Requisite of soil temperature knowledge for the areas where default measurement is not realized, and also the necessity of completing the missing data during the period of hardware failure lead us to the judgement of the relation between the daily average soil temperature measured at different depths at agroclimatological stations. The completing of time series scale 1962 to 2006 of soil temperatures was processed for agrometeorological station Vizovice. For the data processing, daily average soil temperature computed based on 7, 14, 21 h measurements during the years 1962 to 2006 were used. On the basis of the correlation relation between soil temperature data measured at depth 5 and 10 cm; 10 and 20 cm; 20 and 50 cm; and 50 and 100 cm, missing data of the time series were completed. Complete time data series can be used for evaluation of soil temperature regime under different conditions of soil and climate.